Apparent digestibility of different ingredients in diets for bullfrog Rana catesbeiana tadpoles - Secco, Edney Murillo [UNESP]; De Stéfani, Marta Verardino [UNESP]; Vidotti, Rose Meire [UNESP] (Wiley, 2005)
The objective of this study was to determine apparent digestibility of protein and energy of ingredients commonly present in rations fed to bullfrog tadpoles Rana catesbeiana such as corn, soybean meal, wheat meal, rice bran, poultry by-product meal, blood meal, fish meal, corn starch and soybean oil. A completely randomized design was used to test ten experimental diets with four replicates. About 30% of the reference diet was replaced by the test ingredients, except for soybean oil that was used at 10% ratio and 0.5% of chromium oxide as inert marker. The values of apparent digestibility coefficient of crude protein (ADCCP) and gross energy (ADCGE) of the protein ingredients were, respectively: fish meal, 81 and 95%; poultry byproduct meal, 82 and 87%; blood meal, 64 and 53%; and soybean meal, 93 and 90%. While for the energetic ingredients, ADCCP and ADCGE, were, respectively: wheat meal, 100 and 72%; rice bran, 57 and 24%; and corn, 84 and 92%. Soybean oil and cornstarch ADCGE values were 70 and 96%, respectively; cornstarch digestibility is highly dependent on feed processing technique. The results showed that the ing redients of plant origin, except for rice bran, had good digestibility, thus indicating that tadpoles can effectively use plant protein. In this trial, the least digestible ingredients were blood meal and rice bran, thus indicating that the use of such ingredients in bullfrog tadpole diets should be limited. © Copyright by the World Aquaculture Society 2005.
Keywords: frog; Anura; Glycine max; Rana catesbeiana; Triticum aestivum; Zea mays